Format Jurnal - Elkha, Format Jurnal (ELKHA : Jurnal Teknik Elektro, 2012)
Abstract Hybrid of fuzzy and PID represent alliance of both controller, used at different condition and also exploit the advantages from each controller. Fuzzy controller more robust even the system has dynamic variation and do not need precision information (model free). (abstrak dalam bahasa Inggris, baik untuk paper yang berbahasa Inggris maupun Indonesia, maksimal 250 kata, 10 points, bold, justified, dan spasi single) (tabulation, untuk semua paragraf 5 mm) To obtain all the advantages of each controller in this paper we proposed switching method or hybrid control of fuzzy and PID controllers so it will to improve the performance of system. Keywords Non-linear, inexact mathematics model, fuzzy controller, PID controller (makasimal 5keyword)